2017
DOI: 10.1136/practneurol-2017-001828
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral arterial gas embolism from attempted mechanical thrombectomy: recovery following hyperbaric oxygen therapy

Abstract: Cerebral arterial gas embolism is a recognised complication of endovascular intervention with an estimated incidence of 0.08%. Its diagnosis is predominantly clinical, supported by neuroimaging. The treatment relies on alleviating mechanical obstruction and reversing the proinflammatory processes that contribute to tissue ischaemia. Hyperbaric oxygen therapy is an effective treatment and has multiple mechanisms to reverse the pathological processes involved in cerebral arterial gas embolism. Symptomatic cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…An alternative interpretation is that these empty spaces represent air bubbles. Such air emboli are difficult to prove from a histopathological point of view but microscopic, asymptomatic (average diameter 30–60 μm) as well as larger and symptomatic air embolism has been reported in conjunction with cerebral angiography ( 31 33 ). This may suggest that the repeated cerebral angiographies resulted in small amounts of air emboli during the MT that either penetrated the occluding thrombus or were incorporated in an occluding but still growing thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative interpretation is that these empty spaces represent air bubbles. Such air emboli are difficult to prove from a histopathological point of view but microscopic, asymptomatic (average diameter 30–60 μm) as well as larger and symptomatic air embolism has been reported in conjunction with cerebral angiography ( 31 33 ). This may suggest that the repeated cerebral angiographies resulted in small amounts of air emboli during the MT that either penetrated the occluding thrombus or were incorporated in an occluding but still growing thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral air embolism is rare and may be prevented by attaching air filters to both the catheter and contrast-medium syringe, slowing the rate of contrast injection, reducing the number of microcatheter runs and ensuring appropriate catheter priming 20. Heparin-induced thrombocytopenia in patients exposed to heparin during several angiograms may also cause thromboembolism during angiography 21…”
Section: Complicationsmentioning
confidence: 99%
“…It has also been described during lung biopsy, atrial ablation, deployment of septal occluders, and cardiopulmonary bypass surgery. 7,8 The reported incidence of symptomatic cerebral gas emboli during intra-arterial intervention is low (0.08%), 9 but such events may be underreported in atherosclerotic patients if incorrectly interpreted as solid thrombotic emboli.…”
mentioning
confidence: 99%
“…Furthermore, diving medicine has shown that prompt hyperbaric oxygen treatment effectively reduces neurologic symptoms after gas embolism. 8 This maneuver could also be attempted in post-TEVAR stroke.…”
mentioning
confidence: 99%
See 1 more Smart Citation